Highly selective N-glucuronidation of four piperazine-containing drugs by UDP-glucuronosyltransferase 2B10. (2nd September 2018) - Lu, Danyi; Dong, Dong; Wu, Baojian
ABSTRACT: Background : N-glucuronidation is known to be an important metabolic pathway for detoxification and elimination of drugs containing aromatic amines. However, the metabolic pathways for piperazine-containing drugs are not fully established. Methods : N-glucuronidation potential of four piperazine-containing drugs, namely two antihistamines (i.e. cyclizine and chlorcyclizine) and two tetracyclic antidepressants (i.e. mirtazapine and mianserin), was determined by using expressed UDP-glucuronosyltransferase (UGT) enzymes and liver microsomes from both human and animals. Results : Among 13 expressed UGT enzymes, only UGT1A4 and UGT2B10 showed conjugating activities toward these four drugs. Reaction phenotyping, chemical inhibition, and activity correlation analysis revealed that UGT2B10 was a high-affinity enzyme and mainly responsible for hepatic N-glucuronidation of all drugs except mianserin. Both UGT1A4 and UGT2B10 were important contributors to mianserin N-glucuronidation. Moreover, significant species differences were observed in N-glucuronidation of all test drugs. In particular, liver microsomes from four experimental animals (i.e. mouse, rat, dog, and monkey) showed none or negligible activity in catalyzing N-glucuronidation of four drugs. Conclusions : UGT2B10 plays a critical role in N-glucuronidation of piperazine-containing drugs. Also, conventional experimental animals might be inappropriate models for studying human N-glucuronidation. Abbreviations: CLint : intrinsic clearance; CLmax : maximal clearance; HLM: human liver microsomes; K m : Michaelis–Menten constant; K i : substrate inhibition constant; MS: mass spectroscopy; NNAL: 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanol; QTOF: Quadrupole time-of-flight; S 50 : the substrate concentration resulting in 50% of V max ; UDP-GlcA: uridine diphosphoglucuronic acid; UGT: UDP-glucuronosyltransferase; UPLC: ultra performance liquid chromatography; V max : maximal velocity.